2018
DOI: 10.1038/s41598-017-18521-5
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a radiation-responsive ‘p53 gateway’ contributing significantly to the radioresistance of lepidopteran insect cells

Abstract: Recently, we have demonstrated that microRNA-31 (miR-31) overexpression is inherent to radiation-induced cell death in the highly radioresistant Sf9 insect cells, and regulates pro-apoptotic Bax translocation to mitochondria. In the present study, we report that at sub-lethal radiation doses for Sf9 cells, miR-31 is significantly downregulated and is tightly regulated by an unusual mechanism involving p53. While ectopic overexpression of a well-conserved Sfp53 caused typical apoptosis, radiation-induced p53 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(66 citation statements)
references
References 51 publications
1
65
0
Order By: Relevance
“…For example, p53-mediated upregulation of miR-34 is known to induce cell death in C. elegans as well as in mammalian cells. Many other miRNAs other than miR-34 family members are now known to be regulated by p53, viz., miR-194, miR-207, miR-107, miR-215, miR-192, miR-16-1, miR-143, miR-145 and miR-216 [35]. It has been shown that p53 transcriptionally induces miR-34 expression, and this induction is important in p53-mediated apoptosis of cancer cells [36,37].…”
Section: Mirna and Cancermentioning
confidence: 99%
“…For example, p53-mediated upregulation of miR-34 is known to induce cell death in C. elegans as well as in mammalian cells. Many other miRNAs other than miR-34 family members are now known to be regulated by p53, viz., miR-194, miR-207, miR-107, miR-215, miR-192, miR-16-1, miR-143, miR-145 and miR-216 [35]. It has been shown that p53 transcriptionally induces miR-34 expression, and this induction is important in p53-mediated apoptosis of cancer cells [36,37].…”
Section: Mirna and Cancermentioning
confidence: 99%
“…The neurotoxicity associated with chemotherapy for breast cancer is also substantiated by the persistent cognitive deficits related to volume reduction in the hippocampal gray matter one year after treatment completion [7]. Also, there is evidence that the reduction in hippocampal volume is associated with a decrease in cognitive function in patients with major depression [8]. The mechanisms underpinning these symptoms need to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The contrast agents have long blood half-life (40 h) that provides better tumour uptake and clearance from the liver when compared to Au NPs. The agents also efficiently accumulate in tumours and provide high contrast vascular tumour imaging [ 44 ]. In the imaging of thyroid diseases and radionuclide therapy, iodine has been routinely used due to its high affinity for thyroid and relatively long half-life (8.01 days).…”
Section: Medical Imagingmentioning
confidence: 99%